2001
DOI: 10.1073/pnas.071527498
|View full text |Cite
|
Sign up to set email alerts
|

A novel site of antibiotic action in the ribosome: Interaction of evernimicin with the large ribosomal subunit

Abstract: rRNA ͉ ribosomal protein ͉ antibiotics ͉ L16 ͉ drug resistance

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

10
97
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 86 publications
(107 citation statements)
references
References 46 publications
(48 reference statements)
10
97
0
Order By: Relevance
“…Resistance to EVN and AVI also occurs via the action of methyltransferases that modify H89 and H91 (13,14). Consistently, both EVN/AVI protect nucleotides within H89 and H91 from chemical modification (11,12), suggesting that these two rRNA helices comprise at least part of the orthosomycin binding site. Additionally, EVN/AVI resistance has been associated with mutations in Arg-51, Ile-52, and Arg-56 of the ribosomal protein L16 in Enterococcus faecalis, E. faecium, S. pneumoniae, and S. aureus (15)(16)(17)(18).…”
mentioning
confidence: 70%
See 2 more Smart Citations
“…Resistance to EVN and AVI also occurs via the action of methyltransferases that modify H89 and H91 (13,14). Consistently, both EVN/AVI protect nucleotides within H89 and H91 from chemical modification (11,12), suggesting that these two rRNA helices comprise at least part of the orthosomycin binding site. Additionally, EVN/AVI resistance has been associated with mutations in Arg-51, Ile-52, and Arg-56 of the ribosomal protein L16 in Enterococcus faecalis, E. faecium, S. pneumoniae, and S. aureus (15)(16)(17)(18).…”
mentioning
confidence: 70%
“…Subsequent in vitro studies revealed that EVN inhibits IF2-dependent 70S initiation complex formation (11,21); however, the inhibitory effect of EVN is not restricted to translation initiation because toeprinting assays indicate that EVN also inhibits translation elongation (22). EVN and AVI do not inhibit puromycin reaction (11,12) and do not compete for binding with antibiotics that target PTC of the ribosome, such as chloramphenicol, linezolid, lincomycin, or…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, given the enormous size and functional complexity of the ribosome, the number of possible antibiotic targets and sites of functional importance is likely to exceed those currently known. The occasional serendipitous discovery of antibiotics acting on novel ribosomal sites and subsequent recognition of the functional significance of such sites support this notion (8,9). Nonetheless, only a few attempts have been made to identify new sites of antibiotic action and to understand the activity of the associated centers in the ribosome (10).…”
mentioning
confidence: 99%
“…Orthosomycins exhibit broad spectrum antibiotic properties against bacterial pathogens and hold therapeutic promise as they have a scaffold differing from other antibiotics and act on alternative targets. The orthosomycin everninomicin binds a unique site on the ribosome (3,4) and is effective against resistant bacteria including methicillin resistant Staphylococcus aureus and vancomycin resistant enterococci (5). The everninomicin A congener (Ziracin) reached phase III clinical trials, but pharmacological complications prevented approval.…”
mentioning
confidence: 99%